Effect of Different pH on Embryogenesis and Hatching Rate of Srikandi Strain Tilapia Eggs (Oreochromis aureus X Oreochromis niloticus) in Incubator - Moch Saad; Fuquh Rahmat Shaleh; Agung Pamuji Rahayu; Norma Aprilia Fanni (Indonesian Journal of Limnology, 2022)
Tilapia (Oreochromis niloticus) is one of the freshwater fish species which is a leading commodity in the aquaculture sector. The use of an incubator in hatching fish eggs can produce seeds with relatively the same age, the environment is more controlled so it will be easier to manipulate environmental factors that can affect hatching eggs to produce seeds of superior quality. This study aims to determine the description of embryogenesis and hatching rate of Srikandi strain tilapia eggs hatched at different pH. The experimental design used was a completely randomized design (CRD). The treatment consisted of four treatments, namely A (pH 6), B (pH 7), C (pH 8) and D (pH 9) with four replications. Statistical analysis used ANOVA (Analysis of Variance) and to find out the difference between one treatment and another, Duncan's Multiple Range Test was performed. The results showed that different pH treatments had an effect on the embryogeensis of Srikandi tilapia and also had a very significant effect on the hatchability of Srikandi tilapia eggs. The average hatchability of Srikandi tilapia eggs was highest in treatment B (pH 7) of 87.5% although it was not significantly different from treatment C (pH 8) of 80%.